Exploring Objective Interpretation: The Poetry of Mala Abdul Karim Mudarris in Nami's Tafsir - Hawramani, Abduldaim Maruf; Hussein, Hataw Hassan; Abdul Mohammed, Atta Ali; Mahmood, Chnwr Ali; Abdullah, Namam Kamaran; Abdullah, Sozyar Naji; Abdalla, Shabaz (Raden Intan State Islamic University of Lampung, Indonesia, 2024)
In this scholarly exploration, we delve into the distinguished Kurdish scholar Mala Abdulkarim Mudarris, known as